Flavonoids, chalcones and phenyl-propanoids in apple and pear flowers - Horváth, Gy.; Farkas, A.; Szabó, Gy. L. (International Journal of Horticultural Science, 2004)
The presence of phloretin-glycosides in the hypanthium and pistil of apple and pear flowers can be verified. Thin layer chromatography is a reliable method for detecting phloretin, gained by acidic hydrolysis. The dominance of phloretin was equally characteristic for flowers in apple (`Sampion', 'Freedom') and pear (Tem-re Bosc', 'Conference') cultivars treated with various bioregulators (Biomit, Bion 50WG, Regalis), no significant difference could be found visually as compared to control samples. Chlorogenic acid and caffeic acid was detected in all apple and pear samples, rutin was present only in pear, and hyperoside was found only in a few apple samples.